Hubungan Pemanfaatan Artificial Intelligence (AI) dengan Kemandirian Belajar Mahasiswa Pendidikan Agama Islam UINSU - Tasya Ramadani; Nazmul Azzahra; Fadhlam Wafi Lubis; Zainal Abidin (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2026)
This study aims to examine the relationship between the utilization of Artificial Intelligence (AI) and the learning independence of Islamic Religious Education (PAI) students at Universitas Islam Negeri Sumatera Utara (UINSU). The rapid development of AI technology in the academic environment has raised important questions regarding its impact on students’ ability to study independently. This research employed a quantitative approach with a correlational method, involving 30 PAI students as respondents selected through accidental sampling. Data were collected using a closed digital questionnaire with a four-point Likert scale and analyzed through descriptive statistics, normality tests, linearity tests, and Pearson Product Moment correlation. The results indicate that the majority of students fall in the moderate-to-high category in terms of AI utilization, accompanied by a corresponding level of learning independence. The correlation analysis yielded a coefficient of r = 0.695, which exceeds the r-table value of 0.361 at the 5% significance level, confirming a significant positive relationship between AI utilization and students’ learning independence. The coefficient of determination showed that AI contributes approximately 48.3% to the development of learning independence, while the remaining 51.7% is influenced by other factors such as internal motivation, campus environment, and teaching methods. These findings suggest that when used wisely and purposefully, AI can serve as an effective cognitive tool that encourages students to explore academic material independently, rather than creating dependency.